Who wants to get involved? Determinants of citizens' willingness to participate in German renewable energy cooperatives - Beate Fischer; Gunnar Gutsche; Heike Wetzel (Philipps-University Marburg, School of Business and Economics, 2020)
This paper analyzes the potential for citizen participation in renewable energy cooperatives and in the energy transition process. We consider representative survey data for more than 4,200 financial decision-makers in German households and analyze (i) differences between members and non-members of renewable energy cooperatives, (ii) non-members' willingness to participate in energy cooperatives, and (iii) factors determining citizen participation in terms of not only voluntary involvement, but also private investments. We find that the lack of familiarity with energy cooperatives among non-members is a limiting factor for the expansion of citizen participation, a finding that indicates the potential of information campaigns. However, we also reveal a substantial participation potential, as about 40% of the non-members who are familiar with the term "energy cooperative" express a high willingness to become involved. Our econometric analysis based on bivariate binary probit models complements the current state of research by showing the relevance of economic preferences such as time preferences, trust, and negative reciprocity. Interestingly, psychological personality traits, measured by the Big Five, are found to be of minor importance. We additionally confirm the findings of earlier work with regard to the relevance of individual environmental values, social contextual factors, and social norms.
Keywords: G11; M14; Q01; Q49; Q56; 330; Citizen participation; community renewable energy; energy transition; Big Five personality traits; economic preferences; social norms